Thermochemistry of BaSm2O4 and thermodynamic assessment of the BaO–Sm2O3 system. Issue 12 (19th June 2018) - Gong, Weiping; Ushakov, Sergey V.; Agca, Can; Navrotsky, Alexandra
Abstract: The BaO–Sm2 O3 system is of interest for the optimization of synthesis of electroceramics. The only systematic experimental study of phase equilibria in the system was performed more than 40 years ago. The reported experimental values of the enthalpy of formation of BaSm2 O4 are in conflict, and the reported compound Ba3 Sm4 O9 has never been confirmed. In this work we synthesized BaSm2 O4 by solid‐state reaction and determined its heat capacity, enthalpy of formation, and phase transitions by differential scanning calorimetry, high‐temperature oxide melt solution calorimetry and ultra‐high‐temperature differential thermal analysis, respectively. We confirmed the existence of Ba3 Sm4 O9 and its apparent stability from 1873 to 2273 K by X‐ray diffraction on quenched laser‐melted samples but were not able to obtain single‐phase material for calorimetric measurements. The CALPHAD method was used to assess phase equilibria in the BaO–Sm2 O3 system, using both available literature data and our new measurements. A self‐consistent thermodynamic database and the calculated phase diagram of the BaO–Sm2 O3 system are provided. This work can be used to model and thus to understand the relationships among composition, temperature, and microstructure for multicomponent systems with BaO and Sm2 O3 . Abstract : The back scattered electron image of Ba3 Sm4 O9 sample after melting in W crucibles in thermal analyzer. The light phase is barium tungsten oxide formed due to reaction with the crucible.